KEKUATAN HUKUM ADAT DALAM PENYELESAIAN TINDAK PIDANA PERKELAHIAN - Dakhi, Andiliskan (LPPM Universitas Nias Raya, 2025)
The village community of Soto'o Hilisimaetano in Indonesia adheres to customary law for resolving conflicts. In 2023, a conflict in Soto'o Hilisimaetano Village was resolved using customary law, based on the author's observations. The legality of the peace was established through a peace agreement signed by both the perpetrator and the victim. The resolution of peace was achieved by adhering to customary law in order to prevent further complication of the situation. This paper aims to assess the efficacy of customary law in adjudicating conflict cases within Soto'o Hilisimaetano Village, Maniamolo District. This study employs a sociological research approach, utilizing primary data gathered through observation, interviews, and document analysis, and employing qualitative data analysis techniques. Based on the research findings and discussion, it can be concluded that the authority of customary law in addressing criminal acts of fighting in Soto'o Hilisimaetano Village, Maniamolo District is absolute and obligatory. This is due to the enduring strength of the traditional governance system in Soto'o Hilisimaetano Village. Failure to comply will result in social repercussions such as minor penalties or expulsion from the village for more severe infractions. The author recommends that addressing the issue of criminal fights in Soto'o Hilisimaetano Village should involve the assistance of security forces, specifically the police, to ensure a proper resolution of the cases.